2016
DOI: 10.1007/s11356-016-7180-5
|View full text |Cite
|
Sign up to set email alerts
|

Response of microalgae to elevated CO2 and temperature: impact of climate change on freshwater ecosystems

Abstract: To estimate the combined effects of elevated CO2 and temperature on microalgae, three typical and worldwide freshwater species, the green alga Scenedesmus acuminatus, the diatom Cyclotella meneghiniana, and the cyanobacterium Microcystis aeruginosa, as well as mixes of these three species were continuously cultured in controlled environment chambers with CO2 at 390 and 1000 ppm and temperatures of 20, 25, and 30 °C. CO2 and temperature significantly affected the production of microalgae. The cell productivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…The LM model showed that the FI of fDOM-2 was significantly positively correlated with diatom abundance (Table 2). It is well known that amino acids can be released by algal activity (Henderson et al 2008;Li et al 2016). The FI of fDOM-2 was also significantly positively correlated with bacterial abundance in the diatom treatment (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 70%
See 1 more Smart Citation
“…The LM model showed that the FI of fDOM-2 was significantly positively correlated with diatom abundance (Table 2). It is well known that amino acids can be released by algal activity (Henderson et al 2008;Li et al 2016). The FI of fDOM-2 was also significantly positively correlated with bacterial abundance in the diatom treatment (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 70%
“…The fDOM-5 components were considered to be tyrosine-like materials (Cory and McKnight 2005;Yamashita et al 2010). Both could be released during algal activity (Li et al 2016;Yamashita and Tanoue 2003), and were good substrates for bacteria (Wetzel 2001;Pérez and Sommaruga 2006). Moreover, bacteria also release the extracellular polymeric substances (EPS) such as carbohydrates and proteins (Elliott et al 2006;Salama et al 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Both the diatoms, P. triconutum and N. ovalis , have been found to display the same compartmentation for isoprenoid biosynthesis, as previously found in higher plants, the red alga Porphyridium cruentum and the chrysophyte Ochromonas danica [ 160 ]. The extracellular carbohydrates of the diatom Cyclotella meneghiniana have been found to increase with elevated CO 2 and temperature [ 161 ]. Inlet pCO 2 have been found to enhance lipid production along with chitin formation in Cyclotella sp.…”
Section: Opportunities and Challenges Of Co 2 Smentioning
confidence: 99%
“…Experimental studies are therefore important tools to test the effects of climate change in aquatic ecosystem (see for example Li et al, 2016;Short et al, 2016). In fact, the majority of these experimental studies have been developed in temperate regions, and thus offer little insight about the impact of climate change in tropical aquatic ecosystems (see Roland et al, 2012).…”
Section: Introductionmentioning
confidence: 99%